Preoperative Progressive Pneumoperitoneum and Botulinum Toxin Type A in Patients With Large Parastomal Hernia - Tang, Fu-Xin; Ma, Ning; Xie, Xing-Xing; Chen, Shuang; Zong, Zhen; Zhou, Tai-Cheng (Frontiers in Surgery, 2021)
Background: Combination of preoperative progressive pneumoperitoneum (PPP) and botulinum toxin type A (BTA) has not been previously reported in the management of large parastomal hernia (LPH). Methods: An observational study was conducted of 16 consecutive patients with LPH between February 2018 and June 2019. All patients were treated with PPP and BTA injections into the lateral abdominal muscles prior to hernia repair. All hernias were repaired using the laparoscopic Sugarbaker technique. Results: Before and after PPP and BTA, the mean volume of the parastomal hernia (VPH) was 1522 and 1644 cc, respectively (P < 0.01), and the mean volume of the abdominal cavity (VAC) was 5847 and 9408 cc, respectively (P < 0.01). An average reduction of 8.4% of the VPH/VAC ratio was observed on computed tomography scan after the combination of PPP and BTA. Imaging showed a significant increase in the mean lateral abdominal muscle length from 13.1 to 17.9 cm/side (P < 0.01). All hernias were surgically reduced with mesh, with no hernia recurrence after (17.6 ± 2.4) months of follow-up. Conclusions: The preoperative combined use of PPP and BTA can increase abdominal volume, decrease the risk of abdominal compartment syndrome after repair, and facilitate laparoscopic closure of LPH.